1992
DOI: 10.1111/j.1365-2249.1992.tb06869.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of transfer of immune complexes from red blood cell CR1 to monocytes

Abstract: SUMMARYComplement receptor I (CRI) oti primate red blood cells (RBC) binds most complement-fixing immune complexes iti the circulation. It has been postulated that by binding them. RBC keep immune complexes in the intravascular space and deliver ihem to the tissue macrophages of the mononuclear phagocyte system. We have developed an in vitro model to study the transfer of RBC-bound immune complexes {heat-aggregated IgG and DNA-anti-DNA) to phagocytic cells (human monocytes).•• Transfer of immune eomplexes from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 36 publications
1
40
0
Order By: Relevance
“…Some studies have suggested that the transfer reaction requires Fc recognition of erythrocyte-bound complexes by fixed tissue macrophages, followed by proteolysis of CR1 (32,37). Still other studies have suggested that the transfer of soluble immune complexes from erythrocytes to monocytes is driven by the greater number of immune complex binding sites available on monocytes relative to erythrocytes and that the transfer reaction is not dependent on factor I or other enzymatic processing of immune complexes (20).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that the transfer reaction requires Fc recognition of erythrocyte-bound complexes by fixed tissue macrophages, followed by proteolysis of CR1 (32,37). Still other studies have suggested that the transfer of soluble immune complexes from erythrocytes to monocytes is driven by the greater number of immune complex binding sites available on monocytes relative to erythrocytes and that the transfer reaction is not dependent on factor I or other enzymatic processing of immune complexes (20).…”
Section: Discussionmentioning
confidence: 99%
“…The requirement of factors H and I to cleave C3b into iC3b and hence unload the immune complexes from erythrocytes has been questioned by previous studies (12,13,24). In our experiments, transfer reactions were conducted with erythrocyte-bound pneumococci and J774A.1 macrophages in the absence of serum.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that CR1 and Fc receptors on phagocytic cells are involved in the transfer reaction of immune complexes (13,39) and that CR3 and CR4 might participate in the clearance of immune complexes. The newly described macrophage receptors CRIg and SIGN-R1 are thought to be critical in the clearance of blood-borne pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…However, the precise cellular mechanisms involved in the transfer of RBC-bound ICs from RBCs to macrophages or phagocytic cells and the generation of CD235 ϩ MPs during this process remain to be elucidated. The transfer mechanism could be driven by a higher number of CR1 copies on the monocyte than on the RBCs (63) or by the close juxtaposition of the macrophage to the RBC-bound ICs that leads to macrophageassociated protease cleavage of CR1 and a release of the IC from the RBC (64). It is possible that instability of RBC membranes may occur during transfer of CR1-bound ICs from erythrocytes to acceptor phagocytic cells via Fc receptors (64,65) and thus trigger RBCs to shed MPs.…”
Section: Cd235mentioning
confidence: 99%